Financial Management of the Tahfizul Qur'an Islamic Boarding School in Sungai Pinang, Riau - Setyaningsih, Rini; Yoza Mandela, Rahmad; Iskandar, Edi (Studia Manageria, 2025)
This study aims to analyze the implementation of financial management at the Tahfizul Qur'an Islamic Boarding School in Sungai Pinang. The methods used are direct observation and literature study. Observations are conducted to understand real financial management practices, while literature studies are used to support theoretical analysis. The stages of data collection are carried out through field visits, interviews with Islamic boarding school administrators, and documentation of financial reports and applicable internal regulations. The data collected are then analyzed qualitatively with a descriptive approach, namely comparing financial management theory with existing practices in Islamic boarding schools. The analysis focuses on the planning system, funding sources, budget allocation, accounting, reporting, supervision, and risk management. The results of the study indicate that financial management at the Tahfizul Qur'an Islamic Boarding School in Sungai Pinang has been managed systematically through three main functions, namely fundraising, fund allocation, and asset management, with various diversified funding sources, including SPP, BOS funds, ZIS, alumni donations, and independent business results. The financial management system implemented includes planning, accounting, reporting, supervision, and risk management in a transparent, accountable manner, and in accordance with sharia principles, thus supporting operational continuity, improving the quality of education, and the social responsibility of the Islamic boarding school towards underprivileged students.